Rhetoric's Demagogue | Demagoguery's Rhetoric: An Introduction. Issue 3 (27th May 2019) - Skinnell, Ryan; Murphy, Jillian
Abstract : Despite varying understandings of who or what a demagogue is or what a demagogue does, it is little surprise that demagoguery has long occupied rhetoricians, who are of course also interested in persuasion, argument, politics, public speech, affect, emotion, ethics, deliberative discourse, and essentially all the other realms of rhetorical action touched by the demagogue. Still, after more than two and a half millennia of deliberation on the matter, rhetoricians are still grappling with demagoguery—how to define it, how to identify who engages in it, how to explain its rhetorical character and effects, how to resist it, and how to reverse it, or if it's even possible to do so. The essays in this issue advance that effort in a time when demagoguery is once again on the rise.